(untitled) (Swiss Medical Weekly, 2019)
INTRODUCTION Drug traffickers are increasingly making use of the human body for illegal drug transport. Three ways of intracorporeal drug transport are practiced, namely “body packing”, “body stuffing” and “body pushing.” Since police and border guards cannot accurately detect intracorporeal drug transport, authorities require medical professionals for examination and radiological imaging. The aim of this retrospective study was to assess outcomes in all presentations of suspected intracorporeal drug transport referred to the Emergency Department (ED) of the University Hospital of Basel. METHODS We screened the electronic health records (EHRs) of all presentations to the ED between 1 January 2008 and 31 December 2017 for combinations of keywords “body”, “pack”, “stuff” and “push” in the diagnosis and history of presenting complaints. All presentations with suspicion of intracorporeal drug transport were included. Patient characteristics, imaging modality and the results of imaging were assessed. Outcomes were length of stay, hospitalisation, admission to the intensive care unit, surgical intervention and mortality. The main outcome was the rate of surgical interventions during follow-up in hospital and in prison. RESULTS We included 363 presentations in 347 patients. The median age was 35 years and 46 (12.7%) were female. Positive results of imaging were found in 81 of 353 (22.9%) presentations assessed by imaging. In four presentations (1.1%), the result of imaging was indeterminate; in 10 presentations, no imaging was obtained owing to lack of consent or pregnancy. We observed 36 instances of body packing, 10 of body stuffing and 15 of body pushing, and 20 mixed or indeterminate presentations. The number of suspected presentations has risen over the last decade, and the relative number of positive results has almost remained stable over the last six years. No severe or life-threatening complications, interventions, or deaths were observed. Among the presentations with positive imaging results, ten (12.3%) were observed in hospital, as compared with four (1.5%) of those with negative results. CONCLUSIONS Presentations have increased over the last decade while no severe complications or deaths were observed. The consistently low complication rate supports outpatient observation. Considering the ongoing discussion in media and politics, we suggest validation of medical, legal, and ethical guidelines.